Da institucionalização da participação cidadã no âmbito da elaboração de políticas públicas de investimento e o impacto no desenvolvimento municipal de João Pessoa - Morais, Maria Christina Filgueira de (2024)
This study analyzed the institutionalization of citizen participation in the public investment policy cycle at the João Pessoa Municipal Executive Branch, through the Executive Secretariat for Popular Participation. The objective was to analyze the positive impact of this participation on municipal development, considering that, in the face of the current economic crisis, essentially, after the COVID-19 pandemic, and the consequent shortage of resources, it is important to be assertive in the recovery of various sectors, with more responsive results for the population, whose primary function, within the reality of the Secretariat, is to guide the investment made, according to the symptomatology of the problem, avoiding generalist actions, which minimizes losses and justifies the importance of this research. With this in mind, the work begins with the development of two topics on the subject of social rights and public policies, and their repercussions on the development process; ending with the last topic, in which a case study was carried out, based on field research at the aforementioned Secretariat, with data collection, reports and guidance from executive managers, for the development and conclusion of the study. In terms of objectives, the methodology used in the research can be classified as descriptive. In terms of procedures, it was initially classified as documentary and bibliographical, combined with empirical research. In terms of approach, it is classified as quati-qualitative, based on observational methods, in terms of data and bibliography; while it is interpretative in terms of theory formulation. The work started from the premise that citizen participation in the social policy cycle is a fundamental right in exercise, since social policies, including public investment policies, as part of the social order, make social rights possible. The result sought was to associate the evolution of development with this participation.